2003
DOI: 10.1023/a:1024998200846
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The main aim of this study was to assess the kinetics of intracellular free calcium (Ca(2+)i) handling by isolated rat hearts rendered ischemic for 30 min followed by 30 min of reperfusion analyzing the upstroke and downslope of the Ca(2+)i transient. Changes in mechanical performance and degradation of membrane phospholipids--estimated by tissue arachidonic acid content--were correlated with Ca(2+)i levels of the heart. The fluorescence ratio technique was applied to estimate Ca(2+)i. The disappearance of mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Our model proposes that cell signaling pathways target the ETC. However, under conditions of stress, such as ischemia/reperfusion, there is an influx of calcium into the mitochondria [48][49][50]. It has been demonstrated that calcium is a potent activator of the mitochondrial ETC [51].…”
Section: Discussionmentioning
confidence: 99%
“…Our model proposes that cell signaling pathways target the ETC. However, under conditions of stress, such as ischemia/reperfusion, there is an influx of calcium into the mitochondria [48][49][50]. It has been demonstrated that calcium is a potent activator of the mitochondrial ETC [51].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia observed in more severe COPD and during exacerbations can increase the risk of cardiac ischemia, and due to altered repolarization, the risk of ventricular arrhythmias and sudden cardiac death [ 199 , 201 , 203 ]. In addition, cardiac ischemia exposes the heart to oxidative stress that causes derangements in cardiomyocyte homeostasis, such as disturbed calcium handling and lipid signaling [ 204 , 205 , 206 ]. Cardiac dysfunction further aggravates tissue hypoxia that perpetuates systemic oxidative stress.…”
Section: Oxidative Stress—a Link Between Copd and Cardiovascular Como...mentioning
confidence: 99%